What is not so (e)strange about Greek as a Balkan language - Joseph, Brian D. (Keria (Ljubljana), 2020)
In a 2013 lecture at Princeton University, distinguished historian Professor Basil Gounaris suggested that in the 19th-20th centuries there was a "troubled relationship" between Greece and the Balkans, and a process of "estrangement" associated with "the transformation of the Greek-orthodox society itself into a Modern Greek nation". This is all very well and good as far as the 19th and 20th centuries are concerned, and as far as the cultural and political side of the development of modern Greece are concerned, but there is a longer history of engagement between Greek peoples and the Balkans and other dimensions to that history. In particular, from a linguistic standpoint, the interactions between Greek speakers and speakers of other languages in the Balkans - Albanian, Slavic, Romance, Indic, and Turkish in particular - had profound effects on the Greek language that last to this very day. Accordingly, I present here a side of Greece, namely the Greek language, that is not estranged from the Balkans, and explore the ways in which Greek has been affected by, and has influenced, other Balkan languages and the ways in which it can be considered to be a Balkan language.
Keywords: Balkan; Balkans; dialects; Greek; grščina; jezikovna zveza; jezikovni stik; language contact; narečja; Sprachbund